2023
DOI: 10.2147/jbm.s397722
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of COVID-19 Convalescent Plasma (CCP) During the Pandemic Era: A Literature Review

Abstract: Worldwide pandemic with coronavirus disease-2019 (COVID-19) was caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). As November 2, 2022, World Health Organization (WHO) received 628,035,553 reported incidents on COVID-19, with 6,572,800 mortalities and, with a total 12,850,970,971 vaccine doses have been delivered as of October 31, 2022. The infection can cause mild or self-limiting symptoms of pulmonary and severe infections or death may be caused by SARS-CoV-2 infection. Simultaneously, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 176 publications
(222 reference statements)
0
2
0
3
Order By: Relevance
“…Before the COVID-19 pandemic, #6 convalescent plasma had been used in the treatment of other viral infections with positive results 29 . For kidney disease patients who are unable to utilize antiviral medications due to contraindications or safety concerns, convalescent plasma is an alternate treatment 30 . Unfortunately, multiple studies have found that convalescent plasma had no impact on the incidence of mortality or composite poor outcomes in COVID-19 patients 31 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the COVID-19 pandemic, #6 convalescent plasma had been used in the treatment of other viral infections with positive results 29 . For kidney disease patients who are unable to utilize antiviral medications due to contraindications or safety concerns, convalescent plasma is an alternate treatment 30 . Unfortunately, multiple studies have found that convalescent plasma had no impact on the incidence of mortality or composite poor outcomes in COVID-19 patients 31 33 .…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients with CKD not only have a worse prognosis but are also more likely to develop acute respiratory distress syndrome or pneumonia 34 . Although a lot of research has been conducted to find a solution for COVID-19, satisfactory results have not been achieved 30 . Therefore, how to help CKD patients, especially ESRD patients, prevent COVID-19 is very important for both doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Полученные данные свидетельствуют о том, что трансфузии ССР наиболее эффективны в условиях отсутствия у пациентов явлений цитокинового шторма и признаков тяжелой мультиорганной недостаточности. Переливание ССР следует рассматривать как актуальное для пациентов с COVID-19, имеющих иммунодефицитные состояния, в том числе у пациентов на фоне полихимиотерапии злокачественного новообразования [1,3,5,7]. ВЫВОДЫ 1.…”
Section: таблица 4 расчет прогностической значимости (гамма-корреляци...unclassified
“…и вызванное коронавирусом типа 2 тяжелого острого респираторного синдрома (severe acute respiratory syndrome coronavirus 2, SARS-CoV 2). Для терапии COVID-19 были использованы различные лекарственные средства, включая противовирусные препараты, кортикостероиды, иммунопрепараты, антибиотики, антикоагулянты, а также плазма переболевших лиц (COVID-19 convalescent plasma, CCP) [1]. Использование ССР на ранних этапах заболевания оказалось эффективным средством лечения, хотя ее клиническая эффективность не всегда была доказана [2][3][4][5][6].…”
unclassified
See 1 more Smart Citation